Use of Refrigerant Blends to Improve Thermal Efficiency of Heat Pump Cycles - Joshua J. Taylor; James K. Carson; Duy K. Hoang; Timothy G. Walmsley; Qun Chen; Don J. Cleland (Chemical Engineering Transactions, 2022)
High temperature heat pumping (HTHP) is a key technology for minimising emissions from industrial process heat. One option for improving thermal efficiency in heat pump cycles is to match temperature profiles of the refrigerant with the heat source and heat sink fluids as closely as possible. For a pure chemical species evaporation occurs essentially at constant temperature, making it difficult to match the temperature profiles of the refrigerant and heat source fluid. However, the evaporation process for refrigerant mixtures occurs over a range of temperatures, and this range can, within limits, be customised for a particular process. This study describes the development of a heat pump model implemented in Python (checked against data generated in Aspen HYSYS) that was used to investigate whether binary mixtures of alkanes are capable of yielding higher COPs and higher exergy efficiency values when compared to each alkane in its pure form as a result of reduced exergy destruction. A general trend for all mixtures was that COP and second-law efficiency were maximised when the mass fraction of the smaller molecule was between 0.1 and 0.3. It was also observed that the trend was magnified when the difference in boiling points between the two constituents increased. For a heat source glide between 35 °C and 40 °C and a heat sink glide between 40 °C and 80 °C, a mixture of 17 % propane and 83 % pentane gave the highest COP of 4.5 and the highest exergy efficiency of 44.7 %.